Internet of Medical Things - Jain, Narendra Kumar (Indian Journal of Pharmaceutical Education and Research, 2025)
Quality healthcare has been universally recognized as a fundamental human right, but sadly, this right is not sufficiently fulfilled globally. The goal of healthcare 4.0 is to completely revolutionize the healthcare delivery system and part of its bigger framework includes the Internet of Medical Things, or IoMT. IoMT devices are changing patient care and the healthcare industry. IoMT is being used by a number of hospitals and clinics to run their healthcare IT systems more profitably and efficiently. On one side these new technologies connect patients and providers much closer, on the other hand they are making feasible new forms of treatments and boosting consumers’ quality of life.
Keywords: Healthcare 4.0; Internet of Medical Things; Internet of Things; Medical devices; Patient monitoring.